(untitled) (International journal of artificial intelligence, 2026)
This article provides information about the fairy tale genre and its development stages. In English literature, the fairy tale genre, author’s fairy tales and their poetic features are analyzed. Tales in folk art and the unique aspects of author’s tales are discussed.